(untitled) (AYUSHDHARA, 2024)
Psoriatic arthritis is an inflammatory disorder that is chronic and progressive, which affects both skin and joints. Approximately 10-15% of patients who have psoriasis also develop an associated inflammation of their joint. Genetics, dietary, lifestyle related, environmental and psychological factors play a major role in pathogenesis. It is characterized by scaly skin lesion, itching, discharge, joint pain, swelling and stiffness. By considering these signs and symptoms, nearly it can be correlate to Dhatugata kusta, is a condition where in Vatapradhana tridosha affects the Gambhira dhatus causing by deterioration of Uttarottara dhatu. Thus, it is necessary to plan a treatment considering all the factors like Dosha, Dushya, Desha, Kala, Bala and Avastha of disease. Samshodhana is renowned for its ability to eradicate diseases at their core by eliminating morbid Doshas. The Doshas that are pacified by Shodhana never recurs; hence repeated Shodhana chikitsa helps in Bahudoshavastha. A 42 year male patient presented with complaints of silvery blackish scaly skin lesion all over the body. Associated with itching, blood mixed serous discharge, foul smell, multiple joint pain and stiffness visited Panchakarma OPD, GAMC Bengaluru. Patient treated with Pachana Deepana, Virechana, Takradhara and Kustaghna Basti. The present case study is intended to understand the accuracy of multimodal Panchakarma approach, which gives promising results and balance the Tridosha by eliminating the root cause of the disease.